Relationship between Anemia and Placenta Previa with Intrauterine Fetal Death at RSKDIA Pertiwi Makassar City in 2022 - Ricda Nurhikmayanti Hamzah; Risna Yunita Asmin (Jurnal EduHealth, 2023)
The high fetal mortality rate is a problem that must be solved. Intrauterine Fetal Death can be caused by various factors including maternal factors, fetal factors, and placental factors. Maternal factors include age, post term pregnancy (> 42 weeks) and diseases suffered by the mother such as anemia, eclampsia, rupture of membranes and others. However, the cause of fetal death needs to be explored so that it can find out concrete steps to reduce fetal mortality as it should. The purpose of this study was to determine the relationship between Anemia and Placenta Previa with Intrauterine Fetal Death at RSKDIA Pertiwi Makassar City. This research method uses a type of research with a case control approach. The population was all mothers who performed pregnancy checks totaling 3,964 pregnant women. With samples, namely the case group: mothers who were diagnosed with domestic violence amounted to 24 mothers, and the control group: mothers who were not diagnosed with domestic violence as many as 24 mothers, so that the total number of samples was 48 mothers. The data analysis was carried out using the chi-square statistical test. The results of the study of the relationship between Anemia and Intrauterine Fetal Death obtained a p value = 0.042 greater than α = 0.05, this means Ho accepted Ha rejected, while the relationship between Placenta Previa with intrauterine fetal death obtained a p value = 0.365 greater than α = 0.05 which means Ho accepted and Ha rejected. The conclusion of this study is that there is no relationship between anemia and Intrauterine Fetal Death and there is no relationship between placenta previa and Intrauterine Fetal Death